Combination notes: market segmentation and equity transfer - Albert Schaber (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2008)
This paper empirically analyzes a particular type of notes observed in securitization transactions: combination notes. Combination notes are formed by combining parts of two or more tranches of securitization transactions, where one part usually consists of a share of the first loss piece. It is analyzed whether combination notes are purely demand driven, or whether combination notes also appear to be structured to enable equity transfer. Results indicate that combination notes serve both purposes: market segmentation severely determines the structuring of combination notes, but risk transfer needs seem to be catered by combination notes as well. Further, an analysis of launch spreads indicates, that the observed equity transfer via combination notes has an impact on the pricing of the ordinary tranches of each deal. This paper makes use of unique data on 126 deals containing 1385 tranches, thereof 398 combination notes.
urn:nbn:de:bvb:19-epub-7956-1
Keywords: G12; G15; G32; 650; combination note; first loss piece; securitization; collateralized debt obligation; security design